Analysis of Student Learning Difficulties in Blended Learning in Classical Mechanics Course - Muhammad Zaki Zamani; Agus Suyudi (Universal Education Jurnal Teaching and Learning, 2024)
This study aims to identify the difficulties experienced by students in Classical Mechanics lectures using blended learning. The research was designed using descriptive quantitative. This research was conducted at one of the Universities in East Java, on 67 Physics Students and 74 Physics Education Students. Data collection techniques were in the form of a closed questionnaire using a Likert scale with five answer options, namely strongly agree (SA), agree (A), neutral (N), disagree (D), and strongly disagree (SD) and equipped with an open questionnaire containing written questions which were then analyzed quantitatively. The results showed that students still experienced difficulties in attending lectures using the blended learning method.